Tropical montane cloud forests : science for conservation and management - Bruijnzeel, Leendert Adriaan; Scatena, F. N.; Hamilton, Lawrence S. (International hydrology series., 2010)
"This volume represents a uniquely comprehensive overview of our current knowledge on tropical montane cloud forests. 74 chapters cover a wide spectrum of topics including cloud forest distribution, climate, soils, biodiversity, hydrological processes, hydrochemistry and water quality, climate change impacts, and cloud forest conservation, management, and restoration. The final chapter presents a major synthesis by some of the world's leading cloud forest researchers, which summarizes our current knowledge and considers the sustainability of these forests in an ever-changing world. This book presents state-of-the-art knowledge concerning cloud forest occurrence and status, as well as the biological and hydrological value of these unique forests. The presentation is academic but with a firm practical emphasis. It will serve as a core reference for academic researchers and students of environmental science and ecology, as well as practitioners (natural resources management, forest conservation) and decision makers at local, national, and international levels"--